Optimizing preparation of renal biopsy specimens for TEM: a time-efficient approach to rapid diagnosis of kidney diseases - Gen Wang; Xiaodong Zhu; Shaoshan Liang; Feng Xu; Dandan Liang; Caihong Zeng (Renal Failure)
Electron microscopic examination of renal biopsies is crucial for the diagnosis of kidney disease. In this study, we present an optimized protocol that significantly reduces processing time to 19.5 h, compared to 120 h with conventional methods, while preserving ultrastructural quality in 55 renal biopsy specimens. The modified method incorporates the use of higher concentrations of fixatives, shortened fixation duration, low-viscosity resin embedding, and the application of uncoated copper grids. Comparative analysis of renal specimens processed using conventional and optimized methods demonstrated equivalent preservation of critical ultrastructural features, including the glomerular basement membranes, podocytes and tubular epithelium. The total processing time was markedly reduced to 19.5 h, compared to several days with conventional methods. This rapid protocol enables timely ultrastructural evaluation of renal biopsies to facilitate prompt diagnosis and decision-making, highlighting the significance of optimizing diagnostic pathology methodologies for enhancing efficiency and maintaining accuracy.